Enhancing Community-Based Rural Tourism through Master planning, Business Models, and Branding in Curug Luhur, Ambarjaya, Sukabumi - Nurhaida, Dida; Rezandi, Fajar; Effendi, Harris; Alfiansyah, Alif; Aryaseta, Ariel; Abdullah, Muhammad Fathir; Valencia, Erin (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background:  This community service program aimed to develop Curug Luhur as a sustainable rural tourism destination in Desa Ambarjaya by strengthening local capacity in participatory spatial planning, business model development, and digital destination branding. The objective was to integrate these components into a community-based tourism framework that supports environmental sustainability, economic viability, and local governance. Contribution: The program empowered 20 local stakeholders, including village officials, community organizations, and the youth group Bina Muda Group, as well as 11 micro, small, and medium enterprises (MSMEs) from culinary, handicraft, and service sectors. It fostered cross-sector collaboration, enhanced community ownership, and supported MSME integration into the local tourism value chain. Method: A participatory action approach was applied, combining Participatory Rural Appraisal (PRA), site surveys and spatial mapping, focus group discussions (FGDs) for master planning and architectural design, business management training using SWOT analysis and the Business Model Canvas (BMC), MSME empowerment activities, and digital branding and social media workshops. Results: The program produced a community-endorsed tourism master plan, participatory architectural design proposals, strategic business models for tourism activities, and a locally grounded destination brand supported by digital promotion tools. Participant evaluation showed high overall satisfaction (average score: 4.6/5), improved entrepreneurial skills, and stronger community commitment to tourism development. Conclusion: The integration of participatory master planning, business model innovation, and digital promotion effectively strengthened the institutional, economic, and promotional foundations of Curug Luhur. This approach demonstrates a replicable model for sustainable, community-driven rural tourism development in Indonesia.